1995
DOI: 10.1002/acp.2350090104
|View full text |Cite
|
Sign up to set email alerts
|

Graphics in written directions: Appreciated by readers but not writers

Abstract: This series of studies investigated the ability of literate adults to exploit communications options that are available to writers but have no counterpart in speech. Specifically it examined people's use of sketches when giving written directions to help a stranger cross town. When writing an informal letter to a friend most directions were given in prose paragraph style 'Nicole Ummelen collaborated in this research while visiting

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…It is possible that the differences in feature frequency across recipient perspectives and cultures resulted from participants' shifts in perspective in light of recipient task demands (Golledge, 1999;Hirtle & Hudson, 1991;Pazzaglia & DeBeni, 2001;Shelton & McNamara, 2004;Siegel & White, 1975;Taylor & Tversky, 1996). To avoid confusion, direction givers and receivers must coordinate their efforts by selecting an appropriate reference frame, assessing the familiarity of the environment, understanding their individual skills and preferences, and making use of communicative conventions for providing directions (Allen, 2000;Carlson-Radvansky & Radvansky, 1996;Golding et al, 1996;Levinson, 1996;Lloyd, 1991;Taylor & Tversky, 1992;Ward et al, 1986;Wright et al, 1995). For instance, Golding et al (1996) found that when approached by a student requesting wayfinding directions, participants asked clarifying questions to be sure they were describing the correct destination and to assess the requester's knowledge of the campus.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…It is possible that the differences in feature frequency across recipient perspectives and cultures resulted from participants' shifts in perspective in light of recipient task demands (Golledge, 1999;Hirtle & Hudson, 1991;Pazzaglia & DeBeni, 2001;Shelton & McNamara, 2004;Siegel & White, 1975;Taylor & Tversky, 1996). To avoid confusion, direction givers and receivers must coordinate their efforts by selecting an appropriate reference frame, assessing the familiarity of the environment, understanding their individual skills and preferences, and making use of communicative conventions for providing directions (Allen, 2000;Carlson-Radvansky & Radvansky, 1996;Golding et al, 1996;Levinson, 1996;Lloyd, 1991;Taylor & Tversky, 1992;Ward et al, 1986;Wright et al, 1995). For instance, Golding et al (1996) found that when approached by a student requesting wayfinding directions, participants asked clarifying questions to be sure they were describing the correct destination and to assess the requester's knowledge of the campus.…”
Section: Discussionmentioning
confidence: 96%
“…People provide a variety of details when giving wayfinding directions, including landmarks, street names, distances, directions, turn descriptions, and commands (Golding, Graesser, & Hauselt, 1996;Lloyd, 1991;Mark & Gould, 1995;Ward, Newcombe, & Overton, 1986;Wright, Lickorish, Hull, & Ummelen, 1995). Moreover, there are marked individual differences in the frequency of each cue (Denis, Pazzaglia, Cornoldi, & Bertolo, 1999;Klein, 1982;Vanetti & Allen, 1988).…”
Section: Introductionmentioning
confidence: 93%
“…Despite well-documented differences between written narrative and oral conversations in general (e.g. Chafe & Danielewicz, 1987;Ellis & Beattie, 1986), previous research has found very few differences between written and oral formats when communication maintains the same discourse focus, such as giving directions to facilitate wayfinding (Hildyard & Hidi, 1985;Wright et al, 1995). Thus, we are confident that the written directions provided here were reasonably similar to the directions they would have provided in other settings, including offering oral directions.…”
Section: Discussionmentioning
confidence: 99%
“…Diwadkar & McNamara, 1997;Montello, Hegarty, Richardson, & Waller, 2004;Presson, DeLange, & Hazelrigg, 1987Presson & Hazelrigg, 1984;Richardson, Montello, & Hegarty, 1999;Sholl & Nolin, 1997; but see Roskos-Ewoldsen, McNamara, Shelton, & Carr, 1998 for contradictory findings). To avoid confusion, direction givers and receivers must coordinate their efforts by selecting an appropriate perspective or frame of reference, assessing the familiarity of the environment, and understanding their individual skills and preferences, as well as cultural conventions for communication (Allen, 2000;Allen, Kirasic, & Beard, 1989;Carlson-Radvansky & Radvansky,1996;Levinson, 1996;Plumert, Pick, Marks, Kintsch, & Wegesin, 1994;Plumert & Strahan, 1997;Taylor & Tversky, 1992;Wright et al, 1995). For instance, Golding et al (1996) found that when approached by a student requesting wayfinding directions, participants asked clarifying questions to be sure that they were describing the correct destination and to assess the requester's knowledge of the campus.…”
Section: Discussionmentioning
confidence: 99%
“…An interesting but still under-researched problem is that writers (or, for that matter, reviewers) may not even have access to the needs and preferences they would have as readers. Wright et al showed this phenomenon in a series of experiments, where receivers of route directions preferred to get a map and information providers stuck to verbal descriptions, even though they were capable of drawing a map [49]. We have seen many other examples of the same phenomenon in formative evaluation studies we conducted.…”
Section: Contextual Factorsmentioning
confidence: 83%